Insomnia remission and improvement of bodily pain in older adults: a randomized clinical trial - Martin F. Bjurstrom; Richard Olmstead; Michael R. Irwin (PAIN Reports)
Abstract. Introduction:. Older adults with insomnia frequently report bothersome pain. Whether insomnia treatment reduces bodily pain in older adults without chronic pain conditions is not known. Objectives:. This randomized controlled trial aimed to determine whether treatment of insomnia disorder with cognitive behavioral therapy for insomnia (CBT-I), as compared with sleep education therapy (SET), yields durable remission of insomnia and reduces moderate pain symptoms over 36 months in older adults with insomnia disorder. Methods:. A community-based sample of 291 adults ages 60 years and older (mean age, 70.1 years; 57.7% female) with insomnia disorder, but no chronic pain condition, were randomized to 2 months of intervention with either CBT-I (n = 156) or SET (n = 135). The primary outcome was change in bodily pain as measured by the short form 36 (SF-36) health survey. Secondary outcome was remission of insomnia continuously sustained over 36 months of follow-up. Results:. Improvements in bodily pain, as indexed by increases in SF-36 scores, were found in CBT-I with insomnia remission (adjusted β = 0.18; 95% CI, 0.004–0.360; P = 0.045) and in SET with insomnia remission (adjusted β = 0.25; 95% CI, 0.035–0.457; P = 0.023) but not in treatment groups without insomnia remission. As compared with those without insomnia remission, insomnia remission was associated with improvements in pain (adjusted β = 0.19; 95% CI, 0.047–0.325; P = 0.009) and with increases in the proportion of participants who achieved a minimal clinically important difference (likelihood ratio χ21,16 = 264.04; P < 0.001). Conclusions:. Sustained remission of insomnia disorder leads to improvements in bodily pain, with the potential to prevent chronic pain disorders in older adults with insomnia. Trial Registration:. ClinicalTrials.gov NCT01641263.